Neuroecology of alcohol risk and reward: Methanol boosts pheromones and courtship success in Drosophila melanogaster. - Keesey, I.W.; Doll, G.; Chakraborty, S.D.; Baschwitz, A.; Lemoine, M.; Kaltenpoth, M.; Svato, A.; Sachse, S.; Knaden, M.; Hansson, B.S. (Science advances, 2025)
Attraction of Drosophila melanogaster toward by-products of alcoholic fermentation, especially ethanol, has been extensively studied. Previous research has provided several interpretations of this attraction, including potential drug abuse, or a self-medicating coping strategy after mate rejection. We posit that the ecologically adaptive value of alcohol attraction has not been fully explored. Here, we assert a simple yet vital biological rationale for this alcohol preference. Flies display attraction to fruits rich in alcohol, specifically ethanol and methanol, where contact results in a rapid amplification of fatty acid-derived pheromones that enhance courtship success. We also identify olfactory sensory neurons that detect these alcohols, where we reveal roles in both attraction and aversion, and show that valence is balanced around alcohol concentration. Moreover, we demonstrate that methanol can be deadly, and adult flies must therefore accurately weigh the trade-off between benefits and costs for exposure within their naturally fermented and alcohol-rich environments.